Extracellular cell-free RNA profile in human large follicles and small follicles - Shi, Huajuan; Pan, Min; Sheng, Yuqi; Jia, Erteng; Wang, Ying; Dong, Juan; Tu, Jing; Bai, Yunfei; Cai, Lingbo; Ge, Qinyu (Frontiers in Cell and Developmental Biology, 2022)
Studies indicated that follicular fluid contain a considerable number of valuable and functional RNAs. However, to date, no studies have reported the variety and characteristics of RNAs in follicular fluid. Furthermore, this study collected twenty four follicular fluid samples from 20 patients undergoing IVF (n = 9) or ICSI (n = 11), including sixteen large follicular fluid and eight small follicular fluid. The cell-free RNA (cfRNA) profile of follicular fluid samples were analysed by RNA sequencing. This result indicated that the concentration of follicular fluid cfRNA ranged from 0.78 8.76 ng/mL, and the fragment sizes were 20 200 nucleotides. The concentration and fragment sizes of large follicular fluid and small follicular fluid were no significantly difference (P > 0.05). The technical replicas correlation of follicular fluid sample ranged from 0.3 0.9. The correlation of small follicular fluid samples were significantly (P < 0.001) lower than that of large follicular fluid samples. This result showed that follicular fluid cfRNA could be divided into 37 Ensemble RNA biotypes. A large number of mRNAs, circRNAs and lncRNAs were identified in follicular fluid, and the number of cfRNAs in large follicular fluid were significantly (P < 0.05) higher than that of small follicular fluid. Furthermore, follicular fluid contained a large amount of intact mRNA and splice junctions. And a large number of tissue-derived RNAs, which are at an equilibrium state of balanced supply and removal in follicular fluid. KEGG pathway analysis revealed that differentially expression cfRNAs were enriched in some pathways, such as throid hormone synthesis, cGMP-PKG signaling pathway, inflammatory mediator regulation of TRP channels. In addition, our further showed that four RNAs (TK2, AHDC1, PHF21A and TTYH1) can serve as a potential indicator to distinguish the follicles of different sizes. ROC curve shown a great potential in predicting the different follicular fluid sizes [area under the curve (AUC) > 0.8]. This study revealed the types of follicular fluid cfRNA and fragment distribution, source of organization and the potential for distinguishing between follicles of different sizes. This results may inform the study of utility and implementation of cfRNA in clinical practice.